The Influence of Shopping Motivation and Shopping Lifestyle on E-Impulsive Buying on the Shopee Marketplace (Case Study of Graha Prima Computer Students) - Bintang, Astina; Jusri, Jusri; Adi, Adi (Candela Edutech Indonesia, 2025)
The Objectives – This study aims to determine 1) The influence of shopping motivation on e-impulsive buying on the Shopee marketplace, 2) The influence of shopping lifestyle on e-impulsive buying on the Shopee marketplace, 3) The influence of shopping motivation & shopping lifestyle simultaneously on e-impulsive buying on the Shopee marketplace. The Methods/approaches – This study uses a quantitative approach with a comparative causal research type. Data were collected through the distribution of offline questionnaires distributed directly. Each variable was measured with a Likert scale and then processed through SPSS 25 where the appropriate data analysis was multiple linear regression analysis, partial t-test, and F-test. The sampling technique used a purposive sampling method with a final sample of 104 respondents using the Slovin formula. The Results – The research results show that shopping motivation and shopping lifestyle, both partially and simultaneously, influence e-impulsive buying. The emergence of positive emotions, the practicality of the Shopee marketplace, the presence of circulating trends, a high level of lifestyle, and the influence of external factors such as advertising, discounts, and prices confirm that these are triggers for e-impulsive buying. The Research Implications – This research contributes to the understanding of e-impulsive buying behavior on the Shopee marketplace. Shopee needs to develop more effective business strategies to address the factors influencing e-impulsive buying, such as considering the influence of shopping motivation and shopping lifestyle.